THE DEGREE OF SECRETORY IMMUNOGLOBULIN A IN BURN PATIENTS WITH PROBIOTIC THERAPY - HARIANI, LYNDA; WAHYUDI, IRAWAN; DOSOSAPUTRO, ISWINARNO; NOER M., SJAIFUDDIN (International Journal of Applied Pharmaceutics, 2019)
Background: One of the problems with burn patients is the impairment of host immunity, which makes difficult to treat. In burns, immunoglobulin A has demonstrated to decrease. Immunoglobulin A is the main product of mucous immune system, which increases viral clearance and decreases bacterial adhesion in the intestine. Probiotics consist of living microflora, which control the balance of lactobacilli and bifidobacteria in the intestine. Instead of producing organic component, increasing the acidity of intestine, mucin and bacteriocin, they also activate the intestinal immune system and secretory immunoglobulin A (sIgA). The goal of this study was to propose that regular intake of probiotic might help to improve the mucous immune system, especially sIgA in intestines in burn patients. Methods: An experimental, double-blind, controlled clinical trial was carried out in 33 burn patients. Those patients were divided into two groups. The first group was given daily probiotic and the second group was given only placebo for 10 days. The treatment began on the 4th day admission, and then, the degree of sIgA was evaluated before treatment and day 14 from fecal specimen. Results: Significant differences between probiotic and control group were observed (p<0.0001). The degree of sIgA in the probiotic group increased 61.25%, and in the control group, it decreased to 36.80%. Conclusion: The mucous immune system, especially sIgA, increases by probiotic intake.